Criando links, tecendo redes, fortalecendo elos: da atenção básica à saúde mental: a construção de uma clínica - Farina, Patrícia (2011)
There are many issues surrounding mental health clinic, since the incorporation of services to the way they should be offered. On one hand it is demanded that we build a competent clinical strategy regarding the prevention and treatment, capable of handling the community issues, on the other hand, mental health is still haunted by the figure of the professional focused on individual assistance, in a closed room unit, at the mercy of referrals. Trying to escape from reference s scheme and cross-reference and under or over recovery of mental-health clinic, we sought in this work, based on the construction of clinical narratives, given from the development of the clinical research s method in Fundamental Psychopathology, to understand "how?" to make a consistent clinical strategy, but flexible and open at the same time, before the problems that arise in the mental health field, in this case, bringing as context a unit of the Family Health Program and a Judicial Asylum, both located in cities in the state of Sao Paulo. We worked on the trajectory of these patients and the path followed by the clinician in these cases, focusing primarily a networking and co-responsibility